2007
DOI: 10.1177/0265532207071513
|View full text |Cite
|
Sign up to set email alerts
|

The relative significance of syntactic knowledge and vocabulary breadth in the prediction of reading comprehension test performance

Abstract: In the componential approach to modelling reading ability, a number of contributory factors have been empirically validated. However, research on their relative contribution to explaining performance on second language reading tests is limited. Furthermore, the contribution of knowledge of syntax has been largely ignored in comparison with the attention focused on vocabulary. This study examines the relative contribution of knowledge of syntax and knowledge of vocabulary to L2 reading in two pilot studies in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
157
3
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(178 citation statements)
references
References 23 publications
13
157
3
1
Order By: Relevance
“…Conversely, there are still a considerable number of engineering students who need help in reading in Pakistan. A number of researchers have recognized engineering students' reading difficulty to vocabulary knowledge and recommended lexical education (Alderson, 2000;Mudray, 2006;Shiotsu & Weir, 2007;Ward, 2009). Liao and Chen (2012) suggested that if engineering university students want to equip themselves in their career development, suitable Science and technology materials need to be provided in the courses for reading practices.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, there are still a considerable number of engineering students who need help in reading in Pakistan. A number of researchers have recognized engineering students' reading difficulty to vocabulary knowledge and recommended lexical education (Alderson, 2000;Mudray, 2006;Shiotsu & Weir, 2007;Ward, 2009). Liao and Chen (2012) suggested that if engineering university students want to equip themselves in their career development, suitable Science and technology materials need to be provided in the courses for reading practices.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is interesting to note that while this phenomenon does not seem to affect L1 readers to enhance RF through CRR at syntactic level (Rasinki, 2003), it might be more detrimental for FL readers. The difference between the RF performance in L1 and FL can be explained by the low vocabulary skills (Lervå g & Aukrust, 2009), poor syntactic knowledge (Shiotsu & Weir, 2007), or diminished cognitive resources of FL readers that are necessary to focus on both meaning and the form during CRR (i.e. attentional and short-term memory, see LaBerge & Samuels, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…Review studies suggest that decoding skills develop faster than comprehension skills, and consequently, FL learners have significantly larger gaps between scores on RF and reading comprehension measures compared with L1 learners (Quirk & Beam, 2012;Reschly et al, 2009). The reason why FL learners lag behind their comprehension skills can be explained by the lack of vocabulary skills (Lervå g & Aukrust, 2009) or syntactic knowledge (Shiotsu & Weir, 2007). In a meta-analysis Melby- Lervag and Lervag (2014) showed that differences between L1 and FL learners are rather small at word decoding level, because of the higher transfer rate of linguistic skills from L1 to FL.…”
Section: Reading Fluency In a Flmentioning
confidence: 99%
“…Originally designed as a diagnostic tool for teachers (Nation, 1983(Nation, , 1990, the VLT has now come to be used as a widely employed instrument amongst teachers and researchers alike to provide an estimate of vocabulary breadth of L2 language learners (Read, 1988;Cobb, 1997;Schmitt & Meara, 1997;Laufer & Paribakht, 1998;Shiotsu & Weir, 2007). However, this is not the intended use of this instrument.…”
Section: Pedagogical Implicationsmentioning
confidence: 99%